CELL MODELS AS AN ETHICAL ALTERNATIVE TO ANIMAL TESTING ANIMALS (CIPEEX, 2025)
Animal experimentation is a practice potentially used in science and in thedevelopment of medicines and cosmetics. However, the decision to useanimals is usually driven by the lack of viable alternatives to achieve the objectivesof the research, which raises complex ethical issues and demands other accessible methods. Advances such as cell cultures, co-cultures, and three-dimensional (3D) cultures, known asorganoids, allow the reproduction of human tissue functions and structures, reducing theuse of animal testing and promoting more ethical practices in science. Thepresent study aimed to analyze new technologies that replace or declinethe use of animals in scientific research, highlighting the importance of cell modelsand their ethical and technological impact. This is a descriptive literature review, conductedbased on the Pubmed and ScienceDirect databases, prioritizing recent publications(2021–2024). After analyzing the articles, it was possible to identify the evolution of in vitro methods,starting with the biocompatibility test, in which a mammalian cell monolayerwas covered with agar to evaluate plastics used in medical and hospital articlesand identify toxic effects on cells. From this, cell cultures emerged,such as monocultures (a single cell type) and co-cultures (interaction betweendifferent cell types). More recently, 3D cultures ororganoids have been developed, structures derived from stem cells that reproduce morphological,functional, and molecular aspects of real organs. With these advances, more accurate approaches have emerged,such as organ-on-a-chip, microfluidic devices that simulate the biochemical and mechanical environmentof human tissues. These models are encouraged by Law15.183/25, which prohibits cosmetic testing on animals in Brazil, promoting an important advancefor predictive science, enabling safety and efficacy at lower cost,with greater agility and, above all, without the use of animals, contributing significantly to theconsolidation of more ethical practices in scientific research. Cell models offereffective and ethical solutions to replace animal experimentation, meeting the conceptof the 3 Rs, characterized as reduction, refinement, andreplacement, which in summary means reducing the number ofanimals used in research, improving the conduct of studies in order to reducesuffering to a minimum, and seeking methods to replace in vivo testing. It is concludedthat well-designed cellular models can offer essential knowledge forareas of study that promote the health and well-being of society, completely replacinganimal experimentation without compromising scientific quality, contributing to theconsolidation of the 3Rs culture in practice.
Keywords: microphysiological systems; cell culture techniques; in vitro techniques